Can Hba1c Act as A Surrogate Marker for Cardiovascular Risk? - Patel, Manish B; Sachora, Wasimahmed M; Pandya, Ashay R; Kothari, Abhimanyu D; Patel, Jigar K (National Journal of Community Medicine, 2014)
Aim: Glycosylated hemoglobin is a used marker for long-term glycemic control. This investigation is an attempt to evaluate the diagnostic value of HbA(1c) in predicting cardiovascular risk Materials and methods:The study was conducted in V.S general hospital. 278 subjectsduringMay 2012 to October 2012, were included in the study. Details regarding to age, gender, duration of diabetes, were taken. Venous blood samples were collected and analyzed for glycosylated hemoglobin (HbA1c), fasting plasma glucose (FPG), Total Cholesterol, Triglycerides, HDL-C and LDL-C and AIP. Results:The total cholesterol and LDL cholesterol were significantly higher in females as compared to male diabetics. TG levels and AIP ratio were raised in the subjects <55 years compared to those >55 years. In cases with duration of diabetes > 6 years HbA1c, total cholesterol, TG,LDL cholesterol and AIP ratio were elevated but only total cholesterol and LDL cholesterol werestatistically significant. All the lipid parameters except HDL cholesterol were higher in subjects with HbA1c >7 % as compared to the group with HbA1c < 7%. Conclusion: The findings indicate that HbA1c can provideauxiliary information about theextent of circulating lipids and AIP, and can thus be used as a predictor of cardiovascular risk in diabetics.